Green sukuk as a macroeconomic narrative: a comparative study of indonesia and the middle east (2021–2025) - Muhammad Sahirul Alim; Hertha Bastiawan; Astrika Erlin; Suhardiono Suhardiono; Aaminudin Saade (Indonesian Counselor Association (IKI), 2025)
Abstract: Green sukuk have become a flagship innovation in Islamic finance, combining Shariah compliance with sustainable development objectives. This paper explores how Indonesia and the Middle East (Saudi Arabia, UAE) frame green sukuk not merely as financing instruments but as macroeconomic narratives that support fiscal credibility, diversification strategies, and global positioning. Using a qualitative comparative case study and drawing on Institutional Theory, Political Economy, and Policy Communication, the analysis synthesizes evidence from Scopus- and SINTA-indexed scholarship (2021–2025), government frameworks, and multilateral reports. Findings reveal two contrasting models: Indonesia presents sukuk as instruments of “growth with responsibility,” embedded in fiscal frameworks and supported by multi-institutional collaboration. The Middle East emphasizes “diversification and prestige,” linking sukuk to megaprojects under Vision 2030 and ambitions to become global green finance hubs. While Indonesia builds legitimacy through transparency and routine reporting, the Gulf relies on centralized authority and symbolic announcements. The study contributes to theory by extending Institutional Theory to show how legitimacy can arise from either bureaucratic layering or centralized state authority, while Political Economy Theory highlights the role of national strategies. Policy implications suggest that hybrid models—combining Indonesia’s accountability with Gulf visibility—could establish global benchmarks for sustainable Islamic finance.